Nursing Therapy in Hallucinations of Schizophrenia Patients A Literature Review - Angga Sugiarto; Suyanta Suyanta; Erna Erawati; Sri Handayani (Poltekkes Kemenkes Semarang, 2020)
Background: Hallucination is a problem that appears in schizophrenia as a positive symptom that must be addressed immediately so as not to disturb the health status. Nursing therapy is the main alternative to resolve hallucinatory problems in schizophrenic patients who are treated at the Mental Hospital.Methods: The method used is literature review with a library of articles or journals from 2010-2019 by searching through Google Scholar, Pro Quest, GALE, EBSCOhost, and Ovid Journal.Results: The results of the synthesis show that nursing therapy can overcome the problem of hallucinations in schizophrenic patients.Conclusion: CBT and group activity therapy as nursing therapy are effective for hallucinations of schizophrenia